The use of wood as a construction material is still the primary choice for most Indonesian people. For the purposes of structural construction, it would require a long span of wood, whereas stock in the market is limited, so usually it is overcomed with joint technique which can be done with type of joint and connector. Kind of joint that is needed to be considered seriously is tensile, shear and moment joint. Nail joint is relatively cheap and easy to be done. Variables which are used to see an - Sucahyo SADIYO; Imam WAHYUDI; Yeyet . (Departemen Hasil Hutan, IPB, 2012)
The use of wood as a construction material is still the primary choice for most Indonesian people. For the purposes of structural construction, it would require a long span of wood, whereas stock in the market is limited, so usually it is overcomed with joint technique which can be done with type of joint and connector. Kind of joint that is needed to be considered seriously is tensile, shear and moment joint. Nail joint is relatively cheap and easy to be done. Variables which are used to see and predict the level of allowable load for a nail joint are diameter and number of nails. Therefore, the objective of this research was to know the influence from the variables to the strength of joints under uni-axial compression loading from 3 wood species. The results showed that double shear connections strength of nangka wood (allowable load per nail and also total load) has the highest value compared with rasamala and sengon. Nangka wood also reached the highest value for maximum crushing strength. Maximum crushing strength had positive relationship with double shear connections strength. Based on the result of this research, maximum crushing strength is applicable to predict the strength of nails. Keywords : allowable load, maximum crushing strength, nails, double shear connections, tensile joint